2018
DOI: 10.4467/20843879pr.18.024.9953
|View full text |Cite
|
Sign up to set email alerts
|

Uwarunkowania satysfakcji z małżeństwa osób w okresie późnej dorosłości. Perspektywa teorii gerotranscendencji Larsa Tornstama – ujęcie wielopoziomowe

Abstract: Uwarunkowania satysfakcji z małżeństwa osób w okresie późnej dorosłości. Perspektywa teorii gerotranscendencji Larsa Tornstama-ujęcie wielopoziomowe Psychological Determinants of Marital Satisfaction among Older Couples. Perspective of Lars Tornstam's Theory of Gerotranscendence-Multilevel Modeling Approach abstract. Studies into the determinants of marital satisfaction are today a significant research area in psychology. The investigations conducted so far involve mainly the couples at the stages of early and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 18 publications
0
9
0
1
Order By: Relevance
“…Sense of self-dignity is seen as one of the key factors supporting positive aging (Draper, 2021). Previous studies on sense of self-dignity among people in the second half of life have shown that it is associated with a higher quality of life (Tadd, 2017), better physical and mental health (Brudek & Steuden, 2018; Cooper et al, 2017), marital satisfaction (Brudek, 2015), readiness to forgive the partner (Brudek & Steuden, 2017a, 2017b), evaluation and course of the treatment process (Kluft, 2018), and the quality of palliative care services (Laitinen et al, 2016). Bearing in mind the above-mentioned numerous positive relationships of sense of self-dignity with various dimensions of good psychosocial functioning of people in the second half of life (aged 50+), it is worth looking for psychological factors responsible for the maintenance and growth of adults’ sense of self-dignity.…”
Section: Gerotranscendence and Religious Meaning System Wisdom Sense ...mentioning
confidence: 99%
“…Sense of self-dignity is seen as one of the key factors supporting positive aging (Draper, 2021). Previous studies on sense of self-dignity among people in the second half of life have shown that it is associated with a higher quality of life (Tadd, 2017), better physical and mental health (Brudek & Steuden, 2018; Cooper et al, 2017), marital satisfaction (Brudek, 2015), readiness to forgive the partner (Brudek & Steuden, 2017a, 2017b), evaluation and course of the treatment process (Kluft, 2018), and the quality of palliative care services (Laitinen et al, 2016). Bearing in mind the above-mentioned numerous positive relationships of sense of self-dignity with various dimensions of good psychosocial functioning of people in the second half of life (aged 50+), it is worth looking for psychological factors responsible for the maintenance and growth of adults’ sense of self-dignity.…”
Section: Gerotranscendence and Religious Meaning System Wisdom Sense ...mentioning
confidence: 99%
“…Wyrażana w praktyce wzmacnia wiarę, że jest się kochanym przez współmałżonka (Dakowicz, 2015b). Im wyższe zdolności w tym względzie są przejawiane przez współmałżonków, tym większe jest prawdopodobieństwo tworzenia satysfakcjonującej ich relacji (Jankowska, Ryś, 2011;Brudek, Korulczyk, Ciuła, 2018;Milani, Hosseini, Matbouei, Nasiri, 2020).…”
Section: Charakterystyka Małżonków O Wyższym Poziomie Zadowolenia Ze ...unclassified
“…These new properties, which are a consequence of the gerotranscendence process, become an important context in the overall balance of life, including the area of marital relations (Lazarus and Lazarus, 2006). As a consequence, what was once the subject of harm and suffering, today, in retrospect, subjected to redefinition, may become the subject of forgiveness that will strengthen the bond between spouses (Brudek, 2015;Brudek and Steuden, 2017). Thus, more complex models, as well as focusing on particular age groups, are required.…”
Section: Personality Traits and Marital Satisfactionmentioning
confidence: 99%
“…The whole scale reliability calculated using the Cronbach's α index is α = 0.96. This present study uses the Polish version of the MSQFOP scale translated by Brudek (2015). The index of internal consistency (Cronbach's α) calculated for the entire scale (20 items) obtained the value α = 0.94.…”
Section: Marital Satisfactionmentioning
confidence: 99%